النظام الانتخابي الجديد كآلية لتفعيل الديمقراطية المحلية في الجزائر - تعديل 2016 - تعديل 2021 - قــــــــــدوج رسيـــــــــــــــــــــــــــــــــم (جامعة المسيلة, 2021)
إصلاح النظام الانتخابي هو العملية الأنسب لتحقيق الديمقراطية المحلية ، فقد حاول المشرع الجزائري من خلال قانون الانتخابات 16-10 قدر الإمكان تنظيم إجراءات العملية الانتخابية و تدارك النقائص و الثغرات ، و من بين أهم هذه التعديلات استحداث هيئة جديدة لتولي مراقبة الانتخابات و التي تعرف بالهيئة العليا المستقلة لمراقبة الانتخابات ، كما سعى إلى وضع القوائم الانتخابية تحت تصرف المترشحين . و بعدها جاء قانون الانتخابات 21-01 الذي جاء بإصلاحات جديدة أهمها القائمة المفتوحة و التي من خلالها تتحقق الديمقراطية المطلقة . Summary: Reforming the electoral system is the most appropriate process for achieving local democracy, the Algerian legislator tried through the electoral law 16-10 as much as possible to organize the procedures of the electoral process and remedy shortcomings and gaps, the most important of which is the creation of a new body to take over the control of the elections, known as the Independent High Electoral Monitoring Authority, and sought to put electoral lists at the disposal of candidates. Then came the Electoral Law 21-01, which introduced new reforms, the most important of which is the open list through which absolute democracy is achieved.
Keywords: النظام الانتخابي -تفعيل الديموقراطية-